Of giants and windmills: an autobiography - Raza, Moosa (New Delhi Niyogi Books, 2022)
This book is an elaborately layered account of Raza's experiences and encounters with maharajas, politicians, tribals, tigers and a variety of other inhabitants of the country.
Keywords: Autobiography